Teacher Participation in Academic Administration at Singapore International School under the Office of the Private Education Commission - พุ่มพวง, สุภาพร; การีเวท, ดร.สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) to study teachers’ participation in academic administration at Singapore International School under the Office of the Private Education Commission; 2) to compare their participation; and 3) to propose guidelines for developing participation in academic administration.           The sample group consisted of 137 teachers in the 2025 academic year. The sample size was determined using the Krejcie & Morgan table (1970:608), followed by Stratified Random Sampling and Simple Random Sampling. The research instrument was a 5-point rating scale questionnaire with a reliability coefficient of 0.978. The statistics used for data analysis included frequency, percentage, Mean, Standard Deviation, and One-way ANOVA.           The results revealed that:• Overall, teachers’ participation in academic administration in Singapore International Schools under the Office of the Private Education Commission was at the highest level (Mean = 4.7, S.D. = 0.204). When examined by aspect, all aspects were rated at the highest level. Ranked from highest to lowest mean scores, these aspects were: instructional management (Mean = 4.72, S.D. = 0.220), measurement and evaluation (Mean = 4.72, S.D. = 0.222), development and utilization of instructional media (Mean = 4.72, S.D. = 0.247), and curriculum development (Mean = 4.67, S.D. = 0.252), respectively.• The comparison of teachers’ participation in academic administration in Singapore International Schools under the Office of the Private Education Commission, classified by educational qualifications and work experience, showed no statistically significant differences overall.